The Complexity Behavior in B2B Platform Ecosystem With Revenue Sharing - Jianli Xiao; Hanli Xiao; Changrong Li (Discrete Dynamics in Nature and Society, 2024)
The prevalence of B2B platform ecosystem has led to the emergence of revenue-sharing contracts as the dominant business model adopted by manufacturers and retailers on these platforms. This paper establishes a dynamic game model of B2B platform ecosystem, comprising one manufacturer and one retailer, where the manufacturer engages in technological investments and the retailer engages in consumption investments, both exhibiting bounded rationality. Through a comprehensive analysis of complex behaviors, the results reveal the following: (1) Adjustment speed of the manufacturer influences the stability of the platform ecosystem, with higher adjustment speeds leading to greater instability. In a stable state of the B2B platform ecosystem, an actor with lower costs tends to make higher investments. (2) Higher investment costs contribute to a more stable B2B platform ecosystem. When the ecosystem stabilizes, increasing investment costs will reduce manufacturers’ investment levels. (3) The retailer revenue sharing parameter exacerbates the instability of the B2B platform ecosystem. This unequal distribution not only impairs manufacturers’ earnings but also disrupts B2B platform ecosystem equilibrium. (4) Market expansion results in B2B platform ecosystem imbalance. As the market size increases, investment levels rise, but this also leads to system instability. Therefore, managers must strike a balance between market expansion and system stability objectives. (5) We incorporate the time-delayed feedback control (TDFC) method to regulate intricate phenomena. The TDFC method proves effective in mitigating chaotic behaviors within B2B platform ecosystem.